Genome-wide analysis of ionotropic receptor gene repertoire in Lepidoptera with an emphasis on its functions of Helicoverpa armigera. (August 2018) - Liu, Nai-Yong; Xu, Wei; Dong, Shuang-Lin; Zhu, Jia-Ying; Xu, Yu-Xing; Anderson, Alisha
Abstract: The functions of the Ionotropic Receptor (IR) family have been well studied in Drosophila melanogaster, but only limited information is available in Lepidoptera. Here, we conducted a large-scale genome-wide analysis of the IR gene repertoire in 13 moths and 16 butterflies. Combining a homology-based approach and manual efforts, totally 996 IR candidates are identified including 31 pseudogenes and 825 full-length sequences, representing the most current comprehensive annotation in lepidopteran species. The phylogeny, expression and sequence characteristics classify Lepidoptera IRs into three sub-families: antennal IRs (A-IRs), divergent IRs (D-IRs) and Lepidoptera-specific IRs (LS-IRs), which is distinct from the case of Drosophila IRs. In comparison to LS-IRs and D-IRs, A-IRs members share a higher degree of protein identity and are distinguished into 16 orthologous groups in the phylogeny, showing conservation of gene structure. Analysis of selective forces on 27 orthologous groups reveals that these lepidopteran IRs have evolved under strong purifying selection (dN/dS≪1). Most notably, lineage-specific gene duplications that contribute primarily to gene number variations across Lepidoptera not only exist in D-IRs, but are present in the two other sub-families including members of IR41a, 76b, 87a, 100a and 100b. Expression profiling analysis reveals that over 80% (21/26) of Helicoverpa armigera A-IRs are expressed more highly in antennae of adults or larvae than other tissues, consistent with its proposed function in olfaction. However, some are also detected in taste organs like proboscises and legs. These results suggest that some A-IRs in H. armigera likely bear a dual function with their involvement in olfaction and gustation. Results from mating experiments show that two HarmIRs (IR1.2 and IR75d) expression is significantly up-regulated in antennae of mated female moths. However, no expression difference is observed between unmated female and male adults, suggesting an association with female host-searching behaviors. Our current study has greatly extended the IR gene repertoire resource in Lepidoptera, and more importantly, identifies potential IR candidates for olfactory, gustatory and oviposition behaviors in the cotton bollworm. Graphical abstract: Image 1 Highlights: 996 IR genes (856 new) were identified from 29 lepidopteran genomes. Lepidoptera IRs could be distinguished into three sub-families: Divergent IRs, Antennal IRs and Lepidoptera-specific IRs. Gene structure, gain, loss and phylogeny of Lepidoptera IRs were characterized. Some H. armigera antennal IRs likely had dual functions of smell and taste. H. armigera IR1.2 and IR75d were identified as potential IR candidates for oviposition host-searching.